The Impact of COVID-19 Pandemic on Educational Activities in Obafemi Awolowo University Ile-Ife Nigeria - Ayotunde David Odewale Odewale; Banji Marcellinus Adepoju; Johnson Oladimeji Edema (CV The Journal Publishing, 2022)
This paper examines the impact of the COVID-19 pandemic on educational activities in the Obafemi Awolowo University (OAU) community during and after the lockdown era. The pandemic affected almost all the facets of life including the educational sector. Though, the school closure during the lockdown is intended to control the spread of the virus but had widespread socio-economic impacts. Primary and secondary data were used for the study. The study revealed that the COVID-19 pandemic is a major factor of disruption in academic calendar this was as a result of the world being faced with the COVID-19 pandemic, which has held the economy at ransom not exempting the educational sector. Hence, the study conclude that the during COVID-19, educational activities in OAU was faced with many challenges as in other higher institution in Nigeria, such as school closure, loss of academic session, poor learning and limited social ties. The study recommended among others; government and the institution`s management should be proactive in ameliorating the negative impact identified in this study and develop measure to improve educational activities.